The Contribution of Loans to Economic Activity. - Gianluca Cafiso (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study the contribution of loans, granted to different borrower groups, to economic activity in the USA over the period 1971q1-2018q4. Significant economic recessions occurred along the period considered, we center our discussion around the recent Global Financial Crisis. Results are delivered through a historical decomposition analysis based on the estimation of a large VAR through Bayesian techniques. Loans to households emerge as the most important driver of economic activity when compared to other groups, mortgages contribute the most with respect to other typologies. The analysis shows that loan shocks have truly undermined economic activity during the Global Financial Crisis.
Keywords: E44; E51; G20; G21; C11; 330; loans; economic activity; households; corporate business; non-corporate business; Bayesian VAR; historical decomposition